Whale in the sky - Siberell, Anne. (New York : Dutton, 1982)
Describes the Northwest Indian totem pole which shows how Thunderbird punished Whale for chasing Salmon and scaring Frog.
"A Unicorn book."
Book Links (A.L.A.)
Booklist
Horn Book
3.4
K-3
Keywords: Indians of North America -- Northwest Coast of North America -- Folklore; Totem poles -- Juvenile literature; Indians of North America -- Northwest Coast of North America -- Folklore; Totem poles; Animals -- Folklore; Indians of North America; Animals; Totems and totemism